PROFILE OF THE TRAUMATIC ATTENDED SERVICES CARRIED OUT BY THE URGENT MOBILE SERVICE: SAMU IN THE CITY OF PEDRAS DE FOGO – PB - Evelly da Silva Olanda, Debora; da Silva Santos, Samara; Quitéria Fernandes Ferreira, Ana; Tavares Fialho Bezerra, Sayonara; Martins de Araújo, Núbia; Lobato de Souza Costa, Debora; Brasileiro Amancio, Zena; Gabriella Lacerda Sales, Maria; Michele de Araujo Pedro, Fabiana; Dayanna Alves Resende, Tamires; Faria Teixeira, Lídia; Nascimento Cardoso, Camila; et al. (Health and Society, 2022)
Introduction: All actions that precede the arrival of the patient in the hospital are attributed to the prehospital care service. Qualified care at the time of occurrence, transportation and prior arrival at the hospital positively influences the morbidity and mortality rates due to trauma and are paramount for the survival of the victim. Objective: To describe the epidemiological profile of traumatic care performed by the basic emergency mobile service in the city of Pedras de Fogo-PB. Methodology: This is a field-based, descriptive, descriptive, retrospective study with a quantitative approach, based on SAMU records, from January 2017 to January 2018. Data collection was performed through an instrument prepared by the researcher that was filled using data obtained. Results: It was observed through this study that the prevalence of traumatic cases attended by the service had as its main cause the motorcycle and the young adult male. Final Considerations: Concluding that data are omitted from the charts and that the quality of care generates patient survival.